Characterization of α-glucosidase inhibitory constituents of the fruiting body of lion's mane mushroom (Hericium erinaceus). (15th November 2020) - Lee, Seul Ki; Ryu, Se Hwan; Turk, Ayman; Yeon, Sang Won; Jo, Yang Hee; Han, Yoo Kyong; Hwang, Bang Yeon; Lee, Ki Yong; Lee, Mi Kyeong
Abstract: Ethnopharmacological relevance: Hericium erinaceus, commonly called lion's mane mushroom, is an edible and medicinal mushroom that has been traditionally used for the treatment of metabolic disorders, gastrointestinal diseases and memory impairment. In this study, potential anti-hyperglycemic constituents were identified to support the traditional usage of H. erinaceus . Materials and methods: The components of H. erinaceus were purified using various column chromatography techniques. The structure of the separated compounds was determined based on spectroscopic data analysis, i.e., 1D and 2D NMR analysis. The anti-hyperglycemic activity of the isolated compounds was evaluated by measuring the inhibitory effects on α-glucosidase activity. Molecular docking analysis was also conducted for elucidation of α-glucosidase inhibitory activity of isolated compounds. Results: Ten compounds including four new compounds, erinacenols A-D (1 –4 ), were isolated from the fruiting bodies of H. erinaceus. Investigation of the anti-hyperglycemic effect of isolated compounds demonstrated that erinacenol D (4 ), 4-[3′, 7′–dimethyl-2′, 6′-octadienyl]-2-formyl-3-hydroxy-5-methyoxybenzylalcohol (6 ), hericene A (7 ), hericene D (8 ) and hericenone D (9 ) strongly inhibited α-glucosidase activity with IC50 values of <20 μM. The structure activity relationship suggested the importance of long side chain for α-glucosidase inhibitory activity. Further analysis by molecular docking demonstrated the interaction of α-glucosidase and isolated compounds, which supported the inhibitory activity of α-glucosidase. Conclusion: Our present study demonstrated the beneficial effect of H. erinaceus by characterization of α-glucosidase inhibitory compounds, including four new compounds. This approach can be valuable support for the traditional use of H. erinaceus for the treatment of diabetes and metabolic diseases, which needs to be clarified by further in-vivo study. Graphical abstract: Image 1 Highlights: Lion's mane mushroom ( Hericium erinaceus ) inhibited α-glucosidase activity. Ten compounds were isolated from the fruiting bodies of H. erinaceus. Four compounds, erinacenols A-D, were newly reported. Long side chain was suggested to be important for the α-glucosidase inhibitory activity. Interaction of α-glucosidase and compounds by molecular docking analysis.